Extraction and Stability Test of Anthocyanin from Buni Fruits (Antidesma Bunius L) as an Alternative Natural and Safe Food Colorants - Amalia, Fera; Afnani, Galih Nur (Journal of Food and Pharmaceutical Sciences, 2013)
Synthetic  dyes  have  widely  been  usedin  food  products.  However,  the  safety  issues regarding  the  use  of  synthetic  dyes  arise.  Buni  (Antidesma  bunius)  which  contains anthocyanins can be an alternative of synthetic dyes. Anthocyanins are red, blue, or violet natural  colorants  from many  types of plants. The aim of  the  study was  to determine  the best  extraction process  and  to  evaluate  the  stability of  anthocyanins  extracted  from  the Buni fruits. Different combinations of the solvents namely aquadest, ethanol, hydrocloride acid,  and  citric  acid  were  used  to  extract  the  anthocyanins.  The  most  appropriate combination of solvent was determined by the analysis of total anthocyanins content and color  intensity  using  UV-Visible  spectrophotometer.  The  stability  of  anthocyanins  was evaluated using different pH values and  temperature. Ethanol at 70% and citric acid at 3% was  the  most  appropriate  combination  for  the  extraction  with  the  highest  total concentration  of  anthocyanin  (0.58%)  and  color  intensity  (0.324).  The  stability  of  the anthocyanins from Buni was affected by the value of pH, which the most stable condition was set at pH values of 4-5.